The Effect of the Vertex Angles of Wedged Indenters on Deformation during Nanoindentation - Xiaowen Hu; Yushan Ni (Crystals, 2017)
In order to study the effect of the angle of wedged indenters during nanoindentation, indenters with half vertex angles of 60°, 70° and 80° are used for the simulations of nanoindentation on FCC aluminum (Al) bulk material by the multiscale quasicontinuum method (QC). The load-displacement responses, the strain energy-displacement responses, and hardness of Al bulk material are obtained. Besides, atomic configurations for each loading situation are presented. We analyze the drop points in the load-displacement responses, which correspond to the changes of microstructure in the bulk material. From the atom images, the generation of partial dislocations as well as the nucleation and the emission of perfect dislocations have been observed with wedged indenters of half vertex angles of 60° and 70°, but not 80°. The stacking faults move beneath the indenter along the direction [ 1 1 ¯ 0 ] . The microstructures of residual displacements are also discussed. In addition, hardness of the Al bulk material is different in simulations with wedged indenters of half vertex angles of 60° and 70°, and critical hardness in the simulation with the 70° indenter is bigger than that with the 60° indenter. The size effect of hardness in plastic wedged nanoindentation is observed. There are fewer abrupt drops in the strain energy-displacement response than in the load-displacement response, and the abrupt drops in strain energy-displacement response reflect the nucleation of perfect dislocations or extended dislocations rather than partial dislocations. The wedged indenter with half vertex angle of 70° is recommended for investigating dislocations during nanoindentation.